A molecular design method based on the COSMO‐SAC model for solvent selection in ionic liquid extractive distillation. Issue 8 (7th April 2016) - Fang, Jing; Zhao, Rui; Su, Weiyi; Li, Chunli; Liu, Jing; Li, Bo
Abstract : In this study, a molecular design method was used to select solvents for extractive distillation. A COSMO‐SAC model was used to screen for prospective solvents from a wide variety of ionic liquids for extractive distillation. Based on the COSMO‐SAC model, the σ‐profile database of ILs was established. Selectivity and solubility were used as the indexes for solvent screening. According to the molecular design method, three suitable extractive distillation solvents were determined for acetonitrile‐water and ethanol‐cyclohexane systems. Vapor ‐ liquid equilibrium experiment were used to test chosen ILs. This study showed that the experimental and design results were consistent with each other. Therefore, this method is effective and applicable to pick ILs solvents for extractive distillation, and the results could provide a theoretical foundation for industrial production. © 2016 American Institute of Chemical Engineers AIChE J, 62: 2853–2869, 2016